Diagnostic Accuracy of Apparent Diffusion Coefficient in Differentiating Malignant from Benign Endometrial Lesions, Taking Histopathology as Gold Standard: Diagnostic Accuracy of Apparent Diffusion Coefficient for Endometrial Lesions - Seyal, Sidra; Siddique, Smeera; Shams, Fariha; Hukam Deen, Sajida; Nasrullah, Zahra; Azam, Fatima (Pakistan Journal of Health Sciences, 2024)
Endometrial cancer is the cancer of the inner lining of the uterus. Histopathology is considered a gold standard invasive diagnostic test for it. However, Magnetic Resonance Imaging (MRI) based Diffusion-Weighted Imaging (DWI) and apparent diffusion coefficients (ADC) values are non-invasive tests that can differentiate malignant endometrial lesions from benign conditions. Objective: To assess the diagnostic accuracy of MR DWI in differentiating benign from malignant endometrial lesions taking histopathology as a gold standard. Methods: This cross sectional study was carried out at Radiology Ward Lahore General Hospital Lahore for six months. A total of 132 women between 25-55 years of age, with abnormal vaginal bleeding were included. In all patients, diffusion-weighted MRI (DE-MRI) of the pelvis was done followed by histopathology. DW-MRI and histopathology findings were compared. Data were analyzed on SPSS 20.0. The Sensitivity, Specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and diagnostic accuracy were measured using 2×2 contingency table. P-value of <0.001 was taken as significant. Results: DW-MRI diagnosed endometrial cancer in 75 patients while 57 patients didn’t show any malignant lesion. Histopathology confirmed endometrial cancer in 79 cases and benign lesion in 53. Out of 75 positive DW-MRI patients, 72 were True Positive (TP). Out of 57 negative DW-MRI patients, 07 were True negative (TN). Sensitivity, Specificity, PPV, NPV and diagnostic accuracy were 91.14%, 94.34%, 96.0%, 97.72% and 92.42% respectively. Conclusions: DWI based apparent diffusion coefficients (ADC) can more accurately diagnose endometrial cancers than benign lesions. Hence it can be useful adjunct for diagnosis of endometrial lesions.